(untitled) (The Research of Medical Science Review, 2025)
Objective: To assess the fracture union in cases of subtrochanteric femoral fractures managed with dynamic condylar screw. Material and methods: This was a case series study and was conducted at Department of Orthopedic Surgery, D. G. Khan Teaching Hospital, DG Khan from June 2021 to December 2021. Total 90 patients with closed subtrochanteric fractures (within the 1 week of fracture), having age from 20-70 years either male or female were selected. Results: Mean age of the patients was 39.53 ± 15.08 years. Mean duration of fracture was 4.10 ± 1.99 days. Out of 90 patients with subtrochanteric fracture, union was noted in 71 (79%) patients. In age group 20-45 years, union rate was 53 (85.48%) and in age group 46-70 years and union rate was 18 (64.29%). Union of fracture was seen in 5 (29.41%) patients, 39 (92.86%) patients and 27 (87.17%) patients respectively in Type A, B and C fractures. Union was strongly (P = 0.000) associated with type of fracture. Higher number of union was noted in type B fracture. Conclusion: A higher rate of fracture union was observed in cases of subtrochanteric femoral fractures treated by fixation with dynamic condylar screw system. Findings of present also revealed that fracture union is not associated with gender. But significant association of fracture union with age group, duration of disease and type of fracture.